A hybrid approach to incorporating climate change and variability into climate scenario for impact assessments - Yohannes Gebretsadik; Kenneth Strzepek; C. Adam Schlosser (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
Traditional 'delta-change' approach of scenario generation for climate change impact assessment to water resources strongly depends on the selected base-case observed historical climate conditions that the climate shocks are to be super-imposed. This method disregards the combined effect of climate change and the inherent hydro-climatological variability in the system. Here we demonstrated a hybrid uncertainty approach in which uncertainties in historical climate variability are combined with uncertainties in climate predictions to conduct more comprehensive climate change impact assessment to hydropower in Zambezi and Congo River basins. Synthetic ensembles of base-case scenarios of the significant climate variables were generated using frequency domain simulation to represent the uncertainty in natural variability. These were combined with large sets of uncertainties in future climate anomalies, hybrid frequency distributions which are based on the full set of the IPCC AR4 global circulation models. Biophysical modeling of water resource systems in both basins was conducted to study the impact of these scenarios. Results from this study indicate that the use of single base-case approach of delta-change technique could substantially underestimate the potential impact of climate change to hydropower. Particularly, assessments for water resource systems in areas with high natural hydroclimatic variability, careful consideration should be given to the natural variability as the combined effect is more pronounced.
Keywords: C63; Q25; Q54; 330; climate change; hybrid uncertainty; Zambezi; Congo